2001
DOI: 10.1034/j.1600-0722.2001.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel rat dentin mRNA coding only for dentin sialoprotein

Abstract: Dentin sialoprotein (DSP) is a major glycoprotein present in the mineralized dentin matrix that is expressed mainly by young and mature odontoblasts. Mutations in the DSP coding regions are linked to Dentinogenesis imperfecta I and II. indicating the importance of DSP in tooth formation. Previous studies have identified multiple mRNA transcripts in dentin that code for both DSP and phosphophoryns (PPs). Using reverse transcriptase-polymerase chain reaction (RT-PCR) to characterize these mRNA transcripts, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…DSP-only transcripts have been reported for rat (32) and pig (24), but no full-length mRNA transcripts encoding only the DPP portion of the protein have ever been identified. In the absence of selective proteolytic degradation of DSP, one might expect that DSP should be the most abundant noncollagenous protein and DPP should be expressed in almost equal amounts.…”
Section: Discussionmentioning
confidence: 99%
“…DSP-only transcripts have been reported for rat (32) and pig (24), but no full-length mRNA transcripts encoding only the DPP portion of the protein have ever been identified. In the absence of selective proteolytic degradation of DSP, one might expect that DSP should be the most abundant noncollagenous protein and DPP should be expressed in almost equal amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported the isolation of cDNA clones that coded only for DSP in rat [27] and porcine [28]. No studies have ever shown convincing evidence that a DSPP transcript undergoes alternative splicing.…”
Section: Gene Structure and Regulationmentioning
confidence: 99%
“…DSPP in the dentin and bone is present as the proteolytically processed fragments: dentin sialoprotein (DSP) and dentin phosphoprotein (DPP), which originate from the N‐terminal and C‐terminal regions of the DSPP amino acid sequence respectively (Macdougall et al , 1997). The major cleavage sites of DSPP are also at the N‐termini of aspartyl residues (Macdougall et al , 1997; Qin et al , 2001; Ritchie and Li, 2001), as in the case of DMP1 processing. DSPP mutation studies in humans and gene ablation experiments in mice have demonstrated that DSPP and/or its processed fragments (DSP and DPP) are critical for the mineralization of dentin (Xiao et al , 2001; Zhang et al , 2001; Sreenath et al , 2003; Suzuki et al , 2009) and bone (Verdelis et al , 2008).…”
Section: Introductionmentioning
confidence: 99%